2005
DOI: 10.1002/jmr.749
|View full text |Cite
|
Sign up to set email alerts
|

Matching fusion protein systems for affinity analysis of two interacting families of proteins: the cohesin–dockerin interaction

Abstract: Cellulosomes are multi-enzyme complexes that orchestrate the efficient degradation of cellulose and related plant cell wall polysaccharides. The complex is maintained by the high-affinity protein-protein interaction between two complementary modules: the cohesin and the dockerin. In order to characterize the interaction between different cohesins and dockerins, we have developed matching fusion-protein systems, which harbor either the cohesin or the dockerin component. For this purpose, corresponding plasmid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
161
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 96 publications
(162 citation statements)
references
References 45 publications
1
161
0
Order By: Relevance
“…A similar study reported insignificant differences in the fused and native enzyme (39). Chimeric proteins that contained type-I or -II cohesins as binding modules were shown to sustain their binding activity (40,41). These data are consistent with our results that the BglA-CohII had but a mild negative effect on the k cat ∕K m ratio, and the fusion protein formed a stable complex with the cellulosome.…”
Section: Discussionsupporting
confidence: 90%
“…A similar study reported insignificant differences in the fused and native enzyme (39). Chimeric proteins that contained type-I or -II cohesins as binding modules were shown to sustain their binding activity (40,41). These data are consistent with our results that the BglA-CohII had but a mild negative effect on the k cat ∕K m ratio, and the fusion protein formed a stable complex with the cellulosome.…”
Section: Discussionsupporting
confidence: 90%
“…The recombinant protein was purified as described above except all buffers were supplemented with 5 mm β-mercaptoethanol. The production of recombinant Cel48S and the CBM3a-Coh construct (CBM3a fused to the type I cohesin3 from CipA, the primary scaffoldin of C. thermocellum) were described previously (9,31,32).…”
Section: Methodsmentioning
confidence: 99%
“…The specificity of all chimaeric dockerin-containing enzymes to their target cohesins was demonstrated in previous works (Pagès et al 1997;Barak et al 2005;Caspi et al 2006Caspi et al , 2008Caspi et al , 2009Haimovitz et al 2008), except for the 6A-t chimaera. To test its specificity, the same procedure using affinity-based ELISA was conducted, and the chimaera was shown to bind selectively to its ScafÁT target, and not to any of the non-matching cohesins (data not shown).…”
Section: Specificity Of the Chimaeric Enzyme-borne Dockerinsmentioning
confidence: 56%
“…The procedure of Barak et al (2005), Caspi et al (2006), was followed. Rabbit anti-Cel6A (diluted 1:20,000 in blocking buffer) was employed as primary antibody for detection of the interaction of the 6A-t dockerin with its cohesin counterpart.…”
Section: Affinity-based Elisamentioning
confidence: 99%
See 1 more Smart Citation